La inclusión al trabajo del adulto mayor en todas sus modalidades contractuales en el sector privado y público sujeto al Código del Trabajo - Sánchez Murillo, Yadira Sesivel (2025)
This study examines the labor inclusion of older adults in Ecuador, with an emphasis on the legal provisions of the 2008 Constitution and the Labor Code. Despite the legal guarantees promoting their labor rights, older adults continue to face significant barriers, such as age discrimination, limited access to training, and non-compliance with labor inclusion quotas in both the public and private sectors. This situation is even more challenging for those who do not receive pensions, increasing their economic and social vulnerability. The main objective of the study is to evaluate whether Ecuador’s legal framework effectively guarantees the labor rights of older adults under various contractual modalities in both the public and private sectors. To achieve this, the current regulations are examined, violations of labor rights within this group are identified, and an analysis is made of how the lack of employment opportunities impacts their personal development and the exercise of their fundamental rights. Additionally, the effectiveness of public policies related to labor inclusion quotas is assessed. The methodology used was qualitative, including interviews with legal experts and a doctrinal-legal analysis. International models of labor inclusion were also compared. The results revealed a gap between the regulations and their effective implementation, which perpetuates the labor exclusion of this group. This study suggests legal reforms to strengthen public policies, ensure the enforcement of quotas, and promote labor training for older adults.